Association analysis of ACE and ACTN3 in elite Caucasian and east Asian swimmers - Wang, G.; Mikami, E.; Chiu, L. L.; de Perini, A.; Deason, M.; Fuku, N.; Miyachi, M.; Kaneoka, K.; Murakami, H.; Tanaka, M.; Hsieh, L L.; Hsieh, S. S.; et al. (Medicine & Science in Sports & Exercise, 2013)
Purpose: Polymorphic variation in the angiotensin-converting enzyme (ACE) and a-actinin-3 (ACTN3) genes has been reported to be associated with endurance and/or power-related human performance. Our aim was to investigate whether polymorphisms in ACE and ACTN3 are associated with elite swimmer status in Caucasian and East Asian populations.